Entrepreneurial Success within the Process of Opportunity Recognition and Exploitation: An expansion of Entrepreneurial Opportunity Recognition Model - Shamsudeen, Kabir; Keat, Ooi Yeng; Hassan, Hazlinda (International Review of Management and Marketing, 2017)
The purpose of this paper is to expand upon existing entrepreneurial opportunity recognition model that builds on the existing theoretical literature, utilises Dubin's theory-building framework. It identifies entrepreneurial awareness and viable business plan as the determinant of entrepreneurial success within the process opportunity recognition and exploitation. Entrepreneurial awareness is the central component of opportunity recognition process. Entrepreneurial awareness and viable business plan, is the basic condition for the success of the opportunity recognition and exploitation process which in turn yielding a successful entrepreneurial outcome. A proposed conceptual model, a set of propositions, and suggestions for further research are provided. Keyword: Entrepreneurial awareness, viable business plan, Opportunity Recognition, Exploitation Process Model JEL Classifications: L2, L26